The lady Eve [videorecording (DVD)] - Sturges, Preston; Stanwyck, Barbara, 1907-1990; Fonda, Henry, 1905-1982; Coburn, Charles (Criterion collection, 2020)
A lady card shark on a transatlantic ocean liner tries to fleece a young millionaire, but ends up falling in love.